Virological point-of-care testing for the developing world. (June 2014) - Baba, Marycelin M; Vidergar, Nina; Marcello, Alessandro
ABSTRACT: : The goal of point-of-care testing is to provide fast, convenient, and easy-to-use diagnostic assays that shorten the turnaround time of intervention. Several diagnostic tests have already migrated from the centralized laboratory to patients' bedside, physician offices and domestic environments in more developed countries. However, the situation is dramatically different in countries of the developing world where lack of facilities and resources still results in diagnosis to be inferred mostly from the symptoms only. Reliable and rapid diagnosis is urgently needed particularly in case of viral diseases with the concrete risk of outbreaks going undetected in the early stages. In this article we will advocate the necessity to implement robust point-of-care testing for viral diseases to overcome the diagnostic gap of less developed countries.